Molecular profiling, antibiotic susceptibility patterns and pathogenic traits of ESBL producing Acinetobacter baumannii Isolated from wastewater discharges from Goranchatbari sub-catchment area in Dhaka city - Rahman, Amanta (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2024.